Gender Differences in Relations among Perceived Family Characteristics and Risky Health Behaviors in Urban Adolescents. Issue 3 (19th December 2016) - Nelson, Kimberly M.; Carey, Kate B.; Scott-Sheldon, Lori A. J.; Eckert, Tanya L.; Park, Aesoon; Vanable, Peter A.; Ewart, Craig K.; Carey, Michael P.
Abstract: Background: Research regarding the role of gender in relations between family characteristics and health risk behaviors has been limited. Purpose: This study aims to investigate gender differences in associations between family processes and risk-taking in adolescents. Methods: Adolescents ( N  = 249; mean age = 14.5 years) starting their first year at an urban high school in the northeastern USA completed self-report measures that assessed family characteristics (i.e., parental monitoring, family social support, family conflict) and health behaviors (i.e., tobacco use, alcohol use, marijuana use, sex initiation) as part of a prospective, community-based study. Multivariate logistic regression models were used to investigate gender differences in associations between the family characteristics and health behaviors. Results: Among males, higher levels of perceived parental monitoring were associated with lower odds of using tobacco and having ever engaged in sex. Among females, higher levels of perceived parental monitoring were associated with lower odds of marijuana use, alcohol use, and having ever engaged in sex. However, in contrast to males, among females (a) higher levels of perceived family social support were associated with lower odds of alcohol use and having ever engaged in sex and (b) higher levels of perceived family conflict were associated with higher odds of marijuana use and having ever engaged in sex. Conclusion: Family processes were more strongly related to health behaviors among adolescent females than adolescent males. Interventions that increase parental monitoring and family social support as well as decrease family conflict may help to protect against adolescent risk taking, especially for females.